Regenesis : feeding the world without devouring the planet - Monbiot, George, 1963- (Penguin Books, 2022)
"Drawing on advances in soil ecology, George Monbiot reveals how our changing understanding of the world beneath our feet could allow us to grow more food with less farming. He meets the people who are unlocking these methods, from the fruit and vegetable growers revolutionizing our understanding of fertility; through breeders of perennial grains, liberating the land from ploughs and chemicals; to the scientists pioneering new ways to grow protein and fat. Together, they show how to transform not only our food system but our entire relationship to the living world"--